PENGARUH MEDIA KARIKATUR TERHADAP KEMAMPUAN MENULIS NASKAH DRAMA PADA SISWA KELAS IX A SMP NEGERI 3 MUARA BUNGO TAHUN PEMBELAJARAN 2017-2018 - Yuliatma Yuliatma (Jurnal Tunas Pendidikan, 2021)
This study aims to determine the effect of caricature media on the ability to write drama scripts in class IX A students of SMP Negeri 3 Muara Bungo in the 2017-2018 school year. The population of this research is the entire class IX which consists of 2 classes with a total of 70 students. The sample of this study was class IX A which was designated as the experimental class with 24 students and class IX B as the control class with 24 students. The method used in this research is the experimental method. The instrument of this study used an essay test. Based on data analysis techniques, the results of the study were an average of 81.54 using caricature media with details of students getting a score of 80-100 very good 16 people (66.67%) and students who scored 66-69 good 8 people (33 ,33%) by grade IX A students of SMP Negeri 3 Muara Bungo in the 2017-2018 academic year. The average value of 71.22 using the lecture model with details of students who scored 80-100 very well 1 person (4.16%), students who scored 66-79 both 21 people (87.5%) and students who scored 56-65 enough for 2 people (8.34%). Caricature media is more influential in writing drama scripts than the lecture model. Next is hypothesis testing > that is (3.45 > 1.676). Thus, the hypothesis reads that there is "The influence of caricature media on the ability to write drama scripts in class IX A students of SMP Negeri 3 Muara Bungo in the 2017-2018 academic year".